PEMBUATAN MATERI PEMBELAJARAN MULTIMEDIA INTERAKTIF BAGI KELOMPOK GURU MADRASAH TSANAWIAH DI KABUPATEN SIGI - Anshori, Yusuf; Dodu, A. Y. Erwin (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2014)
Education curriculum requires that teachers can take advantage of information and communication technologies in education. The reality there are many teachers who have not been able to operate and use information and communication technologies, especially in terms of learning. The activities of Ipteks Bagi Masyarakat aims to improve the knowledge of teachers in the using of information and communication technologies in terms of making the learning material. The method used is the training, evaluation and mentoring. Knowledge transfer that is making learning materials using Microsoft Office PowerPoint, Wondershare Quiz Creator and Adobe After Effect. Base on assessment and mentoring, from 20 teacher trainees, about 85% of teachers can operate and use Microsoft Office applications Powerpoint, Wondershare Quiz Creator and able to create interactive multimedia learning materials. Keywords:Kurikulum, pembelajaran, ipteks bagi masyarakat, wondershare quiz creator, multimedia interaktif.